1996
DOI: 10.1016/s0741-5214(96)80036-x
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of the external carotid artery after carotid endarterectomy: Implications for management

Abstract: We conclude from these data that averting external CEA during standard CEA does not result in significant progression of ECA stenosis or occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 9 publications
3
41
0
1
Order By: Relevance
“…Mid-to long-term follow-ups were primarily focused on patency rates of ICA and restenosis rates of carotid stents. Only a few studies (12)(13)(14)(15)(16) have evaluated ECA status following carotid interventions. The present study added valuable information to our limited knowledge of ECA status following carotid interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Mid-to long-term follow-ups were primarily focused on patency rates of ICA and restenosis rates of carotid stents. Only a few studies (12)(13)(14)(15)(16) have evaluated ECA status following carotid interventions. The present study added valuable information to our limited knowledge of ECA status following carotid interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Ascer e cols. 127 encontraram associação entre VPS < 150 cm/s com obstruções menores que 50% da ACE e VPS maiores que 250 cm/s com obstruções maiores que 60%.…”
Section: Freire E Cols Recomendação Para a Quantificação Pelo Ultrasunclassified
“…5) ECA occlusion or intimal flap after CEA presents as a potential source for either chronic embolization or a site for extended thrombosis and embolization in the acute situation. 5,6) Amongst some technical variables in performing CEA, the method of removing plaque at the ECA has not been subject to a uniform approach, with a simple transection of the plaque at the orifice, blind endarterectomy into the lumen of the artery, or eversion endarterectomy; all being potential options for completing the endarterectomy in this area. 1,6) The ECA is not usually treated in the same meticulous manner as the ICA during endarterectomy of the carotid bifurcation, where it is mostly endarterectomized in a blinded fashion.…”
Section: )mentioning
confidence: 99%
“…The interpretation of ECA disease was obtained from cross-sectional and longitudinal B-mode ultrasound imaging, as well as from Doppler PSV measurements, based on the measurements of Ascer et al, who contributed a set of duplex-scan PSV criteria for ECA stenosis, on the basis of the magnetic resonance angiography of 60 arteries: <150 cm/s ≤50% stenosis, 150 cm/s to 250 cm/s = 50% to 74% stenosis, and ≥250 cm/s = ≥75% stenosis. 1,6) Ascer et al reported a 100% ECA patency rate and an 18% incidence rate of 50% stenosis and a 10% incidence rate of 75% residual or operatively produced ECA stenosis in the first month after CEA with simple transection of the plaque at the ECA orifice. 1) Our results were comparable with those of only one patient, having what seemed to be residual plaque from surgery detected by the first post operative scan, done within 6 weeks after surgery.…”
Section: )mentioning
confidence: 99%